2015
DOI: 10.1002/lt.24107
|View full text |Cite
|
Sign up to set email alerts
|

First experience of liver transplantation with type 2 donation after cardiac death in France

Abstract: Organ donation after unexpected cardiac death [type 2 donation after cardiac death (DCD)] is currently authorized in France and has been since 2006. Following the Spanish experience, a national protocol was established to perform liver transplantation (LT) with type 2 DCD donors. After the declaration of death, abdominal normothermic oxygenated recirculation was used to perfuse and oxygenate the abdominal organs until harvesting and cold storage. Such grafts were proposed to consenting patients < 65 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 39 publications
11
76
0
3
Order By: Relevance
“…The use of liver grafts from donors suffering CA is expanding as a result of extracorporeal perfusion systems. Fondevila et al and Savier et al have successfully used NRP in 34 and 13 uncontrolled DCD LTs, respectively, with a no‐touch period of 5 minutes . On the other hand, Carter et al have reported 15 LTs from ECMO‐supported DBD donors with a 1‐year graft survival of 93%, and several other studies report similar results .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The use of liver grafts from donors suffering CA is expanding as a result of extracorporeal perfusion systems. Fondevila et al and Savier et al have successfully used NRP in 34 and 13 uncontrolled DCD LTs, respectively, with a no‐touch period of 5 minutes . On the other hand, Carter et al have reported 15 LTs from ECMO‐supported DBD donors with a 1‐year graft survival of 93%, and several other studies report similar results .…”
Section: Discussionmentioning
confidence: 95%
“…For ALT, a cutoff of 4‐fold of the upper limit of normal has been adopted by Fondevila et al, whereas Savier et al have defined this limit at 200 IU/L . Although serum lactate is considered to be a marker of adequate perfusion and hepatic clearance, these groups have placed little importance on this factor, probably because its concentration during NRP may be altered by reflux from extra‐abdominal regions . Recent studies on normothermic machine perfusion have used serum lactate levels for ex situ evaluation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present model, CA is sudden, as is the case in human uDCD. In uDCD, given the abrupt and unexpected nature of arrest, the donor and liver undergo a very prolonged period of warm ischemia, and the risk for the development of ischemic biliary complications in the posttransplant period is very high if aggressive donor recovery and maintenance and strict organ selection criteria are not employed . Although this model lacks the “agonal phase” seen in the other clinical scenario of cDCD, it is unlikely that the addition of an agonal phase would have changed anything with regard to fibrin deposition (or, in this case, the lack thereof).…”
Section: Discussionmentioning
confidence: 99%
“…A protocol of uncontrolled (Maastricht 2) DCD donation was launched in LT in French pilot centers in 2010 with a standardized national protocol. To date, only 20 LTs with uncontrolled DCD donors have been performed with a substantial rate of graft loss . Procurement of controlled DCD organs (Maastricht 3) was authorized in France in 2014.…”
Section: Organ Donation In Francementioning
confidence: 99%